Importance of a Rapid and Accurate Diagnosis in Strongyloides Stercoralis and Human T-Lymphotropic Virus 1 Co-infection: A Case Report and Review of the Literature - Quintero, Olga; Berini, Carolina A.; Waldbaum, Carlos; Avagnina, Alejandra; Juarez, María; Repetto, Silvia; Sorda, Juan; Biglione, Mirna (Frontiers in Microbiology, 2017)
Strongyloides (S.) stercoralis and hman T lymphotropic virus 1 (HTLV-1) share some endemic regions particularly in South America and are mostly diagnosed elsewhere in immigrants from endemic areas such as Peru. This co-infection has not been documented in Argentina although both pathogens are endemic in the Northwest. We present a case of S. stercoralis. and HTLV-1 co-infection with an atypical initial presentation due to gastrointestinal symptoms which presented neither eosinophilia nor the presence of larvae in stool samples in a non-endemic area for these infections. A young Peruvian woman living in Buenos Aires attended several emergency rooms and finally ended up admitted in a gastroenterology ward due to incoercible vomiting, diarrhea, abdominal pain, fever and weight loss. Gastrointestinal symptoms started 3 months before when she returned to Argentina from a trip to Peru. She presented malnutrition and abdominal distension parameters. HIV-1 and other immunodeficiencies were discarded. The serial coproparasitological was negative. Computed tomography showed diffuse thickening of duodenal and jejunal walls. At the begining, vasculitis was suspected and corticosteroid therapy was initiated. The patient worsened rapidly. Skin, new enteral biopsies, and a new set of coproparasitological samples revealed S. stercoralis. Then, HTLV-1 was suspected and infection was confirmed. Ivermectin and albendazole were administrated, until the stool sample remained negative for 2 weeks. Larvae were not observed in fresh stool, Ritchie method, agar culture nor PCR one week post-treatment. Although she required initial support with parenteral nutrition due to oral intolerance she slowly progressed favorably. It has been highly recommended to include a rapid and sensitive PCR strategy in the algorithm to confirm Strongyloides infection, which has demonstrated to improve early diagnosis in patients at-risk of disseminated strongyloidiasis.